Cerebral Folate Deficiency Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Neurologists and geneticists at the University of Barcelona, Spain and other centers analyzed cerebral folate levels in 584 children with neurologic disorders that required diagnostic lumbar puncture.